Structure prediction and characterization of thermostable aldehyde dehydrogenase from newly isolated Anoxybacillus geothermalis strain D9 - Rosli, Nur Ezzati; Mohamad Ali, Mohd Shukuri; Ahmad Kamarudin, Nor Hafizah; Masomian, Malihe; Latip, Wahhida; Saadon, Shazleen; Raja Abd Rahman, Raja Noor Zaliha (Multidisciplinary Digital Publishing Institute, 2022)
In nature, aldehyde dehydrogenase (ALDH) is widely distributed and mainly involved in the oxidation of aldehydes. Thermostability is one of the key features for industrial enzymes. The ability of enzymes to withstand a high operating temperature offers many advantages, including enhancing productivity in industries. This study was conducted to understand the structural and biochemical features of ALDH from thermophilic bacterium, Anoxybacillus geothermalis strain D9. The 3D structure of A. geothermalis ALDH was predicted by YASARA software and composed of 24.3% β-sheet located at the center core region. The gene, which encodes 504 amino acids with a molecular weight of ~56 kDa, was cloned into pET51b(+) and expressed in E.coli Transetta (DE3). The purified A. geothermalis ALDH showed remarkable thermostability with optimum temperature at 60 °C and stable at 70 °C for 1 h. The melting point of the A. geothermalis ALDH is at 65.9 °C. Metal ions such as Fe3+ ions inhibited the enzyme activity, while Li+ and Mg2+ enhanced by 38.83% and 105.83%, respectively. Additionally, this enzyme showed tolerance to most non-polar organic solvents tested (xylene, n-dedocane, n-tetradecane, n-hexadecane) in a concentration of 25% v/v. These findings have generally improved the understanding of thermostable A. geothermalis ALDH so it can be widely used in the industry.